The role of m6A and m6Am RNA modifications in the pathogenesis of diabetes mellitus - Benak, Daniel; Benakova, Stepanka; Plecita-Hlavata, Lydie; Hlavackova, Marketa (Frontiers in Endocrinology, 2023)
The rapidly developing research field of epitranscriptomics has recently emerged into the spotlight of researchers due to its vast regulatory effects on gene expression and thereby cellular physiology and pathophysiology. N 6 -methyladenosine (m 6 A) and N 6 ,2'-O-dimethyladenosine (m 6 Am) are among the most prevalent and well-characterized modified nucleosides in eukaryotic RNA. Both of these modifications are dynamically regulated by a complex set of epitranscriptomic regulators called writers, readers, and erasers. Altered levels of m 6 A and also several regulatory proteins were already associated with diabetic tissues. This review summarizes the current knowledge and gaps about m 6 A and m 6 Am modifications and their respective regulators in the pathophysiology of diabetes mellitus. It focuses mainly on the more prevalent type 2 diabetes mellitus (T2DM) and its treatment by metformin, the first-line antidiabetic agent. A better understanding of epitranscriptomic modifications in this highly prevalent disease deserves further investigation and might reveal clinically relevant discoveries in the future.